Alat Peraga Sebagai Upaya Peningkatan Pemahaman Konsep Peserta didik Pada Materi Mekanika Fluida - Suci Prihatiningtyas; Heny Ekawati Haryono (SEJ (Science Education Journal), 2019)
This research is aimed to increase students' understanding of the concepts of fluid mechanics by applying teaching aids. The research method uses pre-experiment. The research design uses the One Group Pretest-Posttest Design. Data collection techniques using the test of understanding the concept of fluid mechanics as many as 10 essay questions. N-gain test is used to determine the increase in understanding of the concepts of learning outcomes before and after being taught using teaching aids. The results showed that learning by using instructional media in the form of fluid mechanics teaching aids influences students' understanding of concepts by 0.71 with high criteria. This proves that there is an increase in students' understanding of the concepts of fluid mechanics.